1989
DOI: 10.1152/jappl.1989.66.5.2045
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen cost of breathing during fatiguing inspiratory resistive loads

Abstract: When a subject breathes against an inspiratory resistance, the inspiratory pressure, the inspiratory flow, and the lung volume at which the breathing task takes place all interact to determine the length of time the task can be sustained (Tlim). We hypothesized that the mechanism actually limiting tasks in which these parameters were varied involved the rate of energy utilization by the inspiratory muscles. To test this hypothesis, we studied four experienced normal subjects during fatiguing breathing tasks pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 0 publications
3
20
1
Order By: Relevance
“…The effect is similar to that resulting from a lung volume increase of 15-20% of vital capacity, which in adults would translate into a 40-50% reduction in diaphragm strength and endurance. 17 The decreased diaphragmatic resting length demonstrated in healthy infants 16 would impair diaphragm strength and is consistent with our finding of a lower Pimax in the prone position. Our results, therefore, suggest that respiratory muscle strength was lower in the prone position; thus, to achieve higher tidal volumes in that position, infants' respiratory efforts must have been more effective.…”
Section: Discussionsupporting
confidence: 90%
“…The effect is similar to that resulting from a lung volume increase of 15-20% of vital capacity, which in adults would translate into a 40-50% reduction in diaphragm strength and endurance. 17 The decreased diaphragmatic resting length demonstrated in healthy infants 16 would impair diaphragm strength and is consistent with our finding of a lower Pimax in the prone position. Our results, therefore, suggest that respiratory muscle strength was lower in the prone position; thus, to achieve higher tidal volumes in that position, infants' respiratory efforts must have been more effective.…”
Section: Discussionsupporting
confidence: 90%
“…24 In adults such an increase in lung volume results in a 40-50% reduction in diaphragm strength and endurance. 25 Thus it is not surprising that we found that PIMAX was lower in the prone than in the supine posture.…”
Section: Discussionmentioning
confidence: 75%
“…Assuming that transdiaphragmatic pressure was similar in both positions, we reasoned that diaphragm work per breath is increased when infants are prone. As the work of breathing increases, the oxygen cost of breathing increases and inspiratory muscle endurance decreases 32. We acknowledge that measurements of tidal volume or transdiaphragmatic pressure in these infants would have strengthened this conclusion.…”
Section: Discussionmentioning
confidence: 81%